Hippocampus and Insula Are Targets in Epileptic Patients With Glutamic Acid Decarboxylase Antibodies - Falip, Mercè; Rodriguez-Bel, Laura; Castañer, Sara; Sala-Padró, Jacint; Miro, Júlia; Jaraba, Sónia; Casasnovas, Carlos; Morandeira, Francisco; Berdejo, Javier; Carreño, Mar (Frontiers in Neurology, 2019)
Antibodies to glutamic acid decarboxylase (GAD ab) have been found in patients with limbic encephalitis (LE) and chronic pharmacoresistant focal epilepsy (FE). The objectives of the study were: 1) analyze the clinical and neuroimaging course of patients with FE+GAD ab, 2) compare these characteristics with a control group, and 3) describe the most affected cerebral areas in structural and functional imaging. Patients with FE + high titers of GAD ab and a follow-up of at least 5 years were selected. Titers of serum GAD ab below 2000 UI/ml were considered high titers. Characteristics of clinical and radiological evolution were studied in comparison to two different control groups: patients with bilateral or with unilateral mesial temporal sclerosis (BMTS or UMTS) of a non-autoimmune origine. Thirteen patients and 17 controls were included (8 BMTS, 9 UMTS). In the patient group, the most frequent focal aware seizures (FAS) were psychic 5/13 (33%). Somatosensorial, motor, and visual FAS were only reported bypatients (4/13:32%) (p:0.045). Musicogenic reflex seizures (MRS) and previous history of cardiac syncope were also only reporte